What would the economy with credit-enhanced interest rates look like? The case of Turkey. (7th August 2020) - Kurowski, Łukasz; Rogowicz, Karol; Smaga, Paweł
ABSTRACT: We verify the potential impact of credit-enhanced monetary policy rule on inflation, GDP and credit dynamics in Turkey (2002Q1—2018Q3), where the Turkish Cental Bank takes into account financial stability in its inflation-targeting strategy. We estimate interest rates from two monetary policy rules (classic and augmented with the exogenous credit-to-GDP gap) with time-varying parameters (TVP) and assess their performance in a TVP-VAR model. The results show that after the global crisis both observed interest rates and those estimated from the Taylor-rule impact inflation and the GDP in a similar way. The central bank's monetary policy after 2010 was in line with the Taylor rule and took into account cyclical systemic risk with increased strength in the monetary transmission mechanism. Yet, before the crisis, both types of Taylor rules indicate that the bank's monetary policy should have been more restrictive.